Neuroimaging pain and analgesia mechanisms in experimental and chronic pain states - Waldman, S (2022)
Chronic pain is a common and debilitating condition, affecting up to half of the UK population. Despite the use of both pharmacological and psychological/cognitive interventions, it is difficult to treat, and there is a clear need for new, effective therapies. The subjective nature of pain reporting makes the discovery and validation of new treatments challenging, but this could be improved by the presence of an objective biomarker of analgesic efficacy.